Poverty Trajectories Experienced by Persons with Mental Illness. Issue 3 (4th May 2017) - Forchuk, Cheryl; Montgomery, Phyllis; Rudnick, Abraham; Lahey, Pam; Cohen, Benita; Schofield, Ruth; Perry, Stewart E.; Coatsworth-Puspoky, Robin; Edwards, Betty; Butzer, Bethany; Meier, Amanda
ABSTRACT: The present study aimed to better understand the relationship between mental illness and poverty by comparing three groups of individuals with mental illness in Canada: those who see their financial status as improving, worsening, or staying the same. This study used a focused ethnography approach to collect qualitative data from 34 focus group participants. Participants highlighted several facilitators and barriers to financial improvement and often described their financial situation as a cycle that was difficult to escape. Results are discussed in terms of policy implications to facilitate both a movement toward mental health and away from poverty.